PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PADA PT. FIFGROUP PASIR PENGARAIAN - sulastri, Tri (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This research was conducted at PT. FIFGROUP Rokan Hulu with the aim of testing the research to determine (1) the effect of transformational leadership style at PT. Sand FIFGROUP Pengaraian (2) Determine the influence of transformational leadership style variable to variable performance. This study uses a method of use of a questionnaire (Questionnaire), intended to obtain primary data from respondents as a research subject of the variables to be measured, namely PT. FIFGROUP with saturated sampling technique with a sample of 28 employees. This study uses a model of TCR (Achievement Level Respondents). Results showed that: (1) The effect of transformational leadership has a significant influence on employee performance. (2) The equation of the results of simple linear regression is Y = 42 039 + 0,081X + e, which means regression coefficient variable Transformational Leadership Style has a positive value This suggests that the increase in variable Transformational Leadership Style positive influence on employee performance. Variables with a performance coefficient of 0.081 directional coefficient is positive towards Transformational Leadership Style.